2021
DOI: 10.1155/2021/8476592
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Changes in Serum RBP4, hs-CRP, and IL-27 Levels and Rosuvastatin in the Treatment of Coronary Heart Disease

Abstract: Objective. To investigate the correlation between changes in serum RBP4, hs-CRP, and IL-27 levels and rosuvastatin in the treatment of coronary heart disease (CHD). Methods. One hundred and twenty patients with CHD admitted in our hospital were selected as the research object, including 60 patients with acute coronary syndrome as the ACS group, and 60 patients with stable angina as the SA group. Another 60 patients without CHD who were examined in our hospital at the same time were included in the non-CHD grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
2
0
3
Order By: Relevance
“…Studies have shown that inflammatory response actives an important part in changing coronary plaques. [40] hs-CRP is an important inflammatory factor and elevated hs-CRP can predict the increasing risk of CHD. Our meta-analysis revealed that ZXGD could decrease hs-CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that inflammatory response actives an important part in changing coronary plaques. [40] hs-CRP is an important inflammatory factor and elevated hs-CRP can predict the increasing risk of CHD. Our meta-analysis revealed that ZXGD could decrease hs-CRP.…”
Section: Discussionmentioning
confidence: 99%
“…При сочетании ИБС с артериальной гипертензией диагностировано увеличение IL-10 до 49,7±2,8 пг/мл против 10,2±3,0 пг/ мл в группе соматических здоровых лиц зрелого возраста [6]. Сообщается также о важной роли в возникновении и развитии ИБС IL-27 [18], IL-23, IL-35 [17], IL-34 [14], но сочетание ИБС с глаукомой не рассматривается, что определяет значимость настоящего исследования.…”
Section: Discussionunclassified
“…Однако изменения цитокинов в крови изучаются, как правило, раздельно среди пациентов с ИБС и среди пациентов с глаукомой. Показано увеличение ряда цитокинов -IL-1β и IL-10 [6], IL-5, IL-6, IL-6R, TNFα, IFNγ [9], IL-25 и IL-27 [18,19] в качестве факторов риска ИБС. Сообщается также об участии интерлейкинов крови в патогенезе глаукомы [3,4].…”
Section: Introductionunclassified
“…35,36 In addition, higher levels of RBP4 and lower levels of GLUT4 were found in EAT, which can increase the harm of cardiovascular diseases. 37 Studies have shown that 38 serum RBP4 positively correlates with the Gensini score, which can reflect the severity of coronary arteries to a certain extent. More importantly, RBP4 and NT-proBNP have the same value in predicting the prognosis of chronic heart failure.…”
Section: Epicardial Adipose Tissue and Diabetes Mellitusmentioning
confidence: 99%